The Importance of Recognizing Wandering Spleen as a Cause of Recurrent Acute Pancreatitis - Vennis Lourdusamy; Dhrumil Patel; Ramon Docobo; Shyamanand Tantry; Dennis Lourdusamy; Saeed Farukh (Case Reports in Gastrointestinal Medicine)
Wandering spleen, as its name suggests, is a rare condition where the spleen wanders in the abdomen and is most commonly found in the inferior quadrant as a palpable mass. It can have varying presentations and commonly presents as splenic torsion and very rarely as acute pancreatitis. It is imperative not to miss this diagnosis as it can lead to life-threatening complications in the form of splenic torsion/infarction. Here we describe a rare manifestation of wandering spleen where a young female presented with recurrent episodes of acute pancreatitis.